2021
DOI: 10.1037/edu0000640
|View full text |Cite
|
Sign up to set email alerts
|

Numerical magnitude understanding in kindergartners: A specific and sensitive predictor of later mathematical difficulties?

Abstract: Difficulties in mathematics are argued to stem from impairments of a specialized system of numerical magnitude representation. This study investigates whether different measures of numerical magnitude understanding in kindergarten uniquely predict mathematical achievement concurrently and 6 months later, and also examines the relative explanatory of each aspect of magnitude understanding. It also examines the utility of such tasks as sensitive and specific predictors of children at risk of mathematical learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 113 publications
1
6
0
Order By: Relevance
“…Number line estimation skills, which are thought to capture the child's understanding of number order and symbol number magnitude, are less accurate in children with MLD. Recently, Bull et al (2021) found this skill to accurately discriminate between children with MLD and typical achievers. The ANS is responsible for representing non‐symbolic quantities and has been argued to support the acquisition of symbolic representations (cf.…”
Section: Sources Of Heterogeneity (And Inconsistency): Why Different ...mentioning
confidence: 99%
“…Number line estimation skills, which are thought to capture the child's understanding of number order and symbol number magnitude, are less accurate in children with MLD. Recently, Bull et al (2021) found this skill to accurately discriminate between children with MLD and typical achievers. The ANS is responsible for representing non‐symbolic quantities and has been argued to support the acquisition of symbolic representations (cf.…”
Section: Sources Of Heterogeneity (And Inconsistency): Why Different ...mentioning
confidence: 99%
“…Importantly, number line estimation performance by young children is one of the best predictors of later math achievement (Booth & Siegler, 2008; Schneider et al, 2018). It predicts kindergartners’ risk for future math learning difficulties (Bull et al, 2020) and differentiates intellectually precocious first graders from their peers with average math achievement (Hoard et al, 2008). Number lines provide a spatial representation of numerical magnitudes, with the direction and distance between numbers reflecting both ordinal and cardinal relations, and both types of knowledge influence the nature and precision of performance on the number line estimation task.…”
Section: Discussionmentioning
confidence: 99%
“…Difficulties with numerical magnitude processing and the concept of number have also been found to characterize children with MLD (e.g., Geary, 2011). For instance, Bull et al (2021; see also, Swanson et al, 2018) found that poor number line estimation skills in kindergarten characterized children at risk of developing MLD in elementary school. Indeed, MLD screeners feature tasks that evaluate basic skills like numerical comparison and nonsymbolic-to-symbolic mapping (e.g., Butterworth & Laurillard, 2010; Nosworthy et al, 2013).…”
Section: Mathematics Learning Disabilities—a Blended Disordermentioning
confidence: 99%
“…We used two measures that have been used widely in studies that have investigated core underlying skills that support the acquisition of mathematical abilities in school-age children. For instance, poor number line estimation skills are thought to characterize children at risk of developing MLD in elementary school(Bull et al, 2021). Similarly, numerical discrimination acuity of children with mathematical difficulties and dyscalculia is significantly poorer than that of their typically achieving peers(Skagerlund & Träff, 2016).In the Number-Line task, children were tasked to indicate on a line where a number at the top should go.…”
mentioning
confidence: 99%